"God, Home, and Country": Women, Historical Memory, and National Identity in English Canada and the United States. Issue 2 (3rd April 2018) - Snell, Rachel A
ABSTRACT: The late nineteenth- and early twentieth-century witnessed efforts to carve out a space for women in the popular construction of national identity in both Canada and the United States. These efforts, including the rediscovery of, and reverence for, Laura Secord as a feminine counterpart to Isaac Brock's sacrifice and loyalty in Canada, and the efforts to establish continuity with figures such as Betsy Ross and Dolley Madison in the United States, recognized the connection between popular historical memory and definitions of national identity. The founding of the Daughters of the American Revolution (DAR) and the Imperial Order Daughters of the Empire (IODE) during this period represents attempts on both sides of the border to assert a uniquely female national identity and label women as both part of the national community and civic participants.